ANALISIS KEMANDIRIAN BELAJAR SISWA PADA MATA PELAJARAN KIMIA DI KELAS X SMA NEGERI 3 SINTANG - Siti Aisah (Universitas Muhammadiyah Pontianak, 2018)
An observation was conducted to the X MIPA students of SMA Negeri 3 Sintang indicated the low learning independence in Chemistry class. This study aimed to investigate the student learning independence and its factors in Chemistry class at SMA Negeri 3 Sintang. This study used the descriptive method of observation case design. The data were collected using direct observation, interview, and documentation. The subjects were 68 students of the X MIPA. The instruments were interview and observation sheets. Before analyzing the data, it was conducted two times observation and interview. The study revealed that the students’ learning independence was significantly increased. It could be seen from their discipline, responsibility, initiation, and motivation. Based on the internal factor for discipline aspect was excellent (90,81%) while the motivation aspect was good (72,07%). The responsibility (44,73%) and initiation (42,81%) aspects were considered satisfactory, however the self-confidence required more improvement (7,2%). In addition, the results of the interview showed that the external factors played a major role in students’ learning independence. The school environment aspect were considered satisfactory (44,60%) while the family environment (66,66%), learning facilities (69,69%), and teacher competence (71,80%) was good category. In conclusion, the students learning independence of the X MIPA student of SMA Negeri 3 Sintang based on the fifth aspect of the internal factors were satisfactory (51,52%), and the external factors were good (63,18%).